2017
DOI: 10.1016/j.cub.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Audiomotor Perceptual Training Enhances Speech Intelligibility in Background Noise

Abstract: Summary Sensory and motor skills can be improved with training, but learning is often restricted to practice stimuli. As an exception, training on closed-loop (CL) sensorimotor interfaces, such as action video games and musical instruments, can impart a broad spectrum of perceptual benefits. Here we ask whether computerized CL auditory training can enhance speech understanding in levels of background noise that approximate a crowded restaurant. Elderly hearing impaired subjects trained for eight weeks on a CL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 66 publications
3
55
0
Order By: Relevance
“…Our Experimental group training was differentiated from the Placebo training in that the feedback reward was determined by participants' neural activity, not by behavioral performance. Similarly to the reports by Whitton et al (2014) and Whitton et al (2017), the present study showed that the effect of neurofeedback training was transferred to SiN performance, while the Placebo group did not show such generalizability. The generalizability of the training effect observed in the present study may indicate that the reinforcement of attentional modulation on cortical responses may improve a key neural strategy for the SiN understanding.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our Experimental group training was differentiated from the Placebo training in that the feedback reward was determined by participants' neural activity, not by behavioral performance. Similarly to the reports by Whitton et al (2014) and Whitton et al (2017), the present study showed that the effect of neurofeedback training was transferred to SiN performance, while the Placebo group did not show such generalizability. The generalizability of the training effect observed in the present study may indicate that the reinforcement of attentional modulation on cortical responses may improve a key neural strategy for the SiN understanding.…”
Section: Discussionsupporting
confidence: 87%
“…Conventional hearing remediations through amplification cannot improve SiN understanding ability (Bentler et al, 2008). Instead, perceptual training is often considered as a solution for SiN difficulties (Whitton et al, 2014;Whitton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…is striking and has now been documented by several independent groups using a variety of speech-on-29 speech masking paradigms, but not with non-speech maskers (Whitton et al, 2017;Strelcyk and Dau, 30 2009;Johannesen et al, 2016). The exact mechanism of FM coding by the auditory pathway is not entirely 31 clear, with some studies suggesting that these FM cues are converted to amplitude modulation cues in 32 the early stages of auditory processing, and hence that the perception of FM relies more on neural 33 envelope cues rather than the neural phase locking to sTFS (Ghitza, 2001;Whiteford, Kreft and Oxenham, 34 2017; Whiteford and Oxenham, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…For example, participants may be required to respond to the speaker's gender regardless of the word spoken, which in the control condition will be neutral (e.g., "cat") and in the incongruent condition will be conflicting (e.g., "woman" spoken by a man). In addition to gender, other auditory dimensions have been used including pitch ("high" vs. "low"), location ("left" vs. "right"), loudness ("loud" vs. "soft"), and even time ("fast" vs. "slow") (Hamers and Lambert, 1972;Pieters, 1981;Morgan and Brandt, 1989;Roberts and Hall, 2008;Whitton et al, 2017). As well as fewer studies reporting the use of the task, there are also direct reports of non-replication.…”
Section: Direct and Conceptual Replications Of Group Effects And Indimentioning
confidence: 99%